Systematic Review: Use of Digital Media as a Means of Communication of Da’wah - Muhajir Sulthonul Aziz; Meithiana Indrasari; Eko Pamuji; E Rizky Wulandari; M Adhi Prasnowo (LPPM Stikosa - AWS, 2022)
Study was carried out with the aim of analyzing the use of digital media as a means of da'wah communication. Obtain some data about the benefits resulting from digital media for da'wah methods in this digital era. In the digital era, the role of digital media is very important in the spread of da'wah. Study uses a PRISMA systematic review approach by collecting several articles from the literature database. From the results of the systematic review analysis with PRISMA, significant results were obtained from the benefits of digital media for da'wah communication facilities. The form of spreading da'wah that is easy and more familiar with the support of good visual displays is the main attraction. The presence of digital media opens up opportunities for new da'i who want to expand their wings to preach widely alongside leading da'i in cyberspace very easily. Digital media makes the audience of connoisseurs of the da'i unlimited, so a lot of digital media becomes a reference for finding new knowledge treasures or just enjoying the beautiful design combined with brief tausyiah of the da'i in it. From the scale of use, Facebook, Instagram and websites still outperform other digital media in terms of their use as a means of communicating da'wah to the community